DUKUNGAN SOSIAL DAN KUALITAS HIDUP PADA LESBIAN DI ORGANISASI PERUBAHAN SOSIAL INDONESIA (OPSI) PROVINSI RIAU - Afritayeni Afritayeni; Sri Rizki Mulyani (Institut Kesehatan dan Teknologi Al Insyirah, 2021)
Lesbian is a term for women who have a sexual orientation to the same sex. The existence of lesbians in Indonesian society is not so prominent compared to gays. Quality of life (being, belonging, becoming) is crucial in lesbians because of the position of lesbians as minorities. Homosexuality is a bridge connecting the HIV virus to a wider population. They tend to have many sex partners and often have sexual relations without status with their partners. The percentage of HIV and AIDS cases according to risk factors in Indonesia in 2017 is homosexual 20.4%. This research is a qualitative research with ethnographic design conducted from March 13 - 06 August 2019. Based on the survey research informants in this study were lesbians, amounting to 3 people and 4 participants. Data collection is done by in-depth interviews with the data validity test carried out by triangulation. The results found that lesbians are not supported and their lives are not quality because that lesbians do not get support from the community and family only support from friends or spouses. The public is expected to get to know more about sexuality especially with regard to lesbian sexual orientation. Studies according to religion, culture, and social norms consider lesbians to be deviant sexual orientations and provide more support for lesbians to be able to carry out positive activities, such as community activities and carrying out spiritual activities in daily life